Neologizmy Białoszewskiego - Sobolczyk, Piotr (Wydawnictwo Naukowe UAM, 2005)
The article is an attempt to reconsider the problem of the literary neologisms on the ground of poetics treated here, according to the hermeneutics and neoidealistic approaches, as an expression of the poet's way of thinking. So far the problem was dealed with linguistics methods and the author prefers to reformulate it using the rethorics language. The material for this attempt is the "linguistic poetry" of Miron Białoszewski (1922-1983) who often used neologisms in order to express his individuality, to create literary concepts or to shorten his expression. The author proposes the following subdivision of the neologisms: the paragramatic neologism, the contextual neologism, the neoetymologic figure, the contaminatio neologism.
Białoszewski's Neologisms